Social media at the workplace: The relationship between techno eustress and employees performance at Pejabat Pendidikan Daerah Jerantut / Ummi Soleha Mohd Lazim - Mohd Lazim, Ummi Soleha (Faculty of Business and Management, 2020)
Social Media at the Workplace : The Relationship between Techno eustress and Employee Performance as a case study at Pejabat Pendidikan Daerah Jerantut. The purpose of this study was to the investigate relationship between techno eustress and employee performance. This final report comprises of five chapters, where the first chapter introduction of the study. In chapter two covers literature review of the study and chapter three covers research methodology. Thus, in chapter four covers the finding and discussion and chapter five covers conclusion, recommendation and suggestion for future research. There are three research objectives and research questions and followed with two research hypothesis for this study. A total of 92 set of questionnaire were distributed to the employees at Pejabat Pendidikan Daerah Jerantut by using simple random sampling. The questionnaire was constructed in both Malay and English. The questionnaire consists of three sections based on the variables of the study. Furthermore, the data gathered from the questionnaire was analyzed by using the Statistical Packages for Social Science (SPSS) Version 20.0. Then the data will be presented in form of frequency, percentage, and mean to show the relationship between techno-eustress and employee performance. Researcher also recommend and suggests management of companies to limit the usage of social media and conduct campaign in order to increase the awareness of using social media at the workplace.